Numismatic Finds at the Cemetery by the Church of St. Peter in Kula Atlagića near Benkovac (Archaeologia Adriatica, 2010)
Numismatic finds recovered during the archaeological research undertaken in 1997 at the cemetery area by the church of St. Peter in Kula Atlagića near Benkovac are published in this paper. There were 19 specimens of coins. The earliest coins can be dated to late Antiquity whereas the latest Venetian soldi were minted in the 17th and 18th centuries for Dalmatia, Albania and Morea. Silver medieval Venetian coins make most of the finds, alongside examples from the cities of Padua, Mantua, Split and Aquileian patriarchate.
Keywords: Kula Atlagića; Benkovac; numismatics; Venetian coins; late Antique coins; medieval coins